KAJIAN HUKUM DUALISME KEWENANGAN DALAM PENEGAKAN HUKUM TINDAK PIDANA PERIKANAN SETELAH DITETAPKAN- NYA UNDANG-UNDANG NOMOR 45 TAHUN 2009TENTANG PERIKANAN - Abdi Afriando; Zulfikar Jayakusuma; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The existence of Indonesia as one of the largest archipelagic countries in the world is a gift from God Almighty who created and is also the owner of the universe. On the third issue requires the establishment of fisheries courts throughout the territory of the Republic of Indonesia fisheries management. In this case the implementation of law enforcement in the fisheries sector becomes very important and strategic in order to support fisheries development. The spirit of the formation of this special justice is also based on the spirit to overcome the crisis of "powerlessness" of the existing justice institutions in responding to various legal issues, especially those related to law enforcement of fisheries criminal acts.The type of research or approach used by the author is normative legal research. Normative legal research is library legal research, in this normative legal research the authors conduct research on legal principles, namely the principle of justice which is simple, fast and low cost. Where the author is guided by the provisions in force. The data source used by the author in this study is secondary data.Settlement of fisheries cases according to Law Number 45 of 2009 concerning Fisheries in court after the investigation files have been submitted by investigators in the field to be transferred to the prosecutor begins since the investigation case files are declared complete, with a maximum time limit of 30 days the public prosecutor submits the case to district court (Article 76 paragraph (9) of the Fisheries Law). By observing that the suspect can only be detained for a maximum of 20 days and the maximum time limit for the prosecution is 30 days, it seems that the public prosecutor in processing the prosecution of fisheries cases has a choice, will use the detention time or the time limit for the prosecution to settle the case. The problem that arises then is when a region that does not have a fisheries court must resolve the problem of fisheries criminal acts through a district court.Settlement of fisheries criminal cases in Indonesia as regulated in Act Number 45 of 2009 concerning Fisheries which states that fisheries court is a special court established to resolve criminal offenses in the field of fisheries.Keywords: Fisheries Court, Investigations, Fisheries Crimes.